Operation behaviours of surgical forceps in continuous curvilinear capsulorhexis. Issue 5 (23rd May 2022) - Zheng, Yu; Lin, Chuang; Guang, Chenhan; Han, Shaofeng; Ma, Ke; Yang, Yang
Abstract: Background: Continuous curvilinear capsulorhexis (CCC) is a delicate ophthalmic procedure which may benefit from robot technology. Measuring the behaviours (physiological tremor, operation force) of surgeons provides baseline data to develop assistive CCC robot. Methods: A forceps with fibre bragg grating and inertial sensors is used to measure the surgeons' behaviours while experts/novices perform CCC on ex‐vivo pig eyes, in‐vivo rabbit eyes and ex‐vivo human lens. Results: In pig/rabbit tests, the root‐mean‐square (RMS) tremor amplitude is 35.26/59.04 μm (expert/novice, transverse), 13.3/20.55 μm (axial). The RMS voluntary force (VF) and involuntary force (IF) are 8.97/17.16 mN, and 0.66/1.90 mN, respectively. In human lens test, the RMS tremor amplitude is 24.0 μm (transverse, expert only), 9.88 μm (axial). The RMS VF and RMS IF are 9.04 mN (expert only) and 0.17 mN, respectively. Conclusions: The expert surgeons have better precision and less operation force.